Report on raising public awareness and participation (Deliverable D20) - Pina, António Manuel Silva (2008)
The purpose of this document is to present actions taken during the Cyclops project lifetime in order to raise public awareness and participation, as well as the outcomes of these actions. Dissemination and outreach have always been considered key points for accomplishing this, ever since the project planning phases. The actions are generally framed in the Work Package devoted to dissemination (WP5), although some of them may well be regarded as a horizontal action of the project.